PENERAPAN APLIKASI DIGITAL DALAM PENYUSUNAN LAPORAN KEUANGAN UMKM DESA TAMIANG - Ranny Meilisa; Nopiandri Nopiandri; Arista Rosalinda (Batara Wisnu : Indonesian Journal of Community Services, 2021)
In the era of IT-based technology and the Internet of Thinks (IoT), the use of Android-based technology that can be accessed anywhere has become a basic human need. An Android-based bookkeeping application can be used as a tool for recording the inflow and outflow of money that can be used easily and applicable for small and medium-sized businesses. Business actors in Tamiang Village (UMKM) are actors who come from various circles. This type of business has a very large turnover, so a tool is needed to manage financial bookkeeping. At this time there are still many business actors who in running their business have not used information technology applications, they still use books to record their finances. The method that will be implemented in this activity is the method of visits, lectures and practice. The purpose of this service is that the community can take advantage of an Android-based financial bookkeeping application, making it easier for recording and being able to find out the progress of the business being run